Abu di Atas Tunggul: Posisi Kelas Pekerja di Dalam dan Luar Museum - Reimena, Randi; Putra, Heru Joni (Puitika, 2024)
This paper serves as a preliminary note on the symptomatic relationship between the representation of the working class in several museums in Sawahlunto and the current condition of the working class in the same city. As an initial exploration, it aims to provide an early reflection on the absence of class consciousness in the narrative of the working class portrayed in these museums. At the same time, the present working-class community in Sawahlunto experiences life inequalities typical of their social class, yet this lived experience also indicates a lack of class consciousness. The parallel absence of this consciousness, both within the museums and in the broader community, warrants serious attention in future research. The inquiry should go beyond merely outlining the causal link between the two phenomena